2019
DOI: 10.1038/s41598-019-48546-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding PCR Processes to Draw Meaningful Conclusions from Environmental DNA Studies

Abstract: As environmental DNA (eDNA) studies have grown in popularity for use in ecological applications, it has become clear that their results differ in significant ways from those of traditional, non-PCR-based surveys. In general, eDNA studies that rely on amplicon sequencing may detect hundreds of species present in a sampled environment, but the resulting species composition can be idiosyncratic, reflecting species’ true biomass abundances poorly or not at all. Here, we use a set of simulations to develop a mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
200
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(229 citation statements)
references
References 67 publications
8
200
1
Order By: Relevance
“…They found that the DNeasy Blood and Tissue Kit was optimal for eDNA extraction in most cases because it is non-toxic, simple, and less costly than other kits. The cost of PowerWater kit is higher than the DNeasy kit, but its PCR inhibitor removal can effectively improve PCR amplification and data quality [15,63]. Stoeckle et al [64] systematically evaluated the influence of different environmental variables and inhibitors and found that the presence of sediment was the main factor responsible for lower eDNA detection in the water samples, regardless of whether flowing or still water was used.…”
Section: Edna Extraction Methodsmentioning
confidence: 99%
“…They found that the DNeasy Blood and Tissue Kit was optimal for eDNA extraction in most cases because it is non-toxic, simple, and less costly than other kits. The cost of PowerWater kit is higher than the DNeasy kit, but its PCR inhibitor removal can effectively improve PCR amplification and data quality [15,63]. Stoeckle et al [64] systematically evaluated the influence of different environmental variables and inhibitors and found that the presence of sediment was the main factor responsible for lower eDNA detection in the water samples, regardless of whether flowing or still water was used.…”
Section: Edna Extraction Methodsmentioning
confidence: 99%
“…First, although RRA may not provide a reliable quantitative proxy in all DNA‐metabarcoding applications (De Barba et al, 2014; Deagle et al, 2019), its use for herbivore diet analysis with trn L‐P6 has been supported by strong correlations between (a) the RRA of food‐plant taxa and the proportional biomass of those taxa consumed by sheep in feeding trials (Willerslev et al, 2014) and (b) the RRA of C 4 grasses and estimates of proportional C 4 ‐plant consumption derived from carbon stable‐isotope ratios, including a nearly 1:1 correlation across seven ruminant and non‐ruminant species in our study system (Kartzinel et al, 2015). Moreover, RRA is less sensitive than presence–absence‐based approaches to the inclusion of low‐abundance reads (including potential sequencing errors and contaminants) and does not require the use of arbitrary thresholds for deciding whether rare taxa are present in or absent from a sample (Deagle et al, 2019; Kelly, Olaf Shelton, & Gallego, 2019). Importantly, we do not compare the absolute value of any diversity metric to those reported in other studies, but instead focus exclusively on the relative patterns of diversity obtained based on many samples that were analysed using identical PCR protocols.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the spatial resolution of our eDNA communities, we used non-metric multidimensional scaling (nMDS) ordination of eDNA indices for all ASVs within each technical replicate (Port et al, 2016). To derive this index, we first normalized taxon-specific ASV counts into proportions within a technical replicate, and then transformed the proportion values such that the maximum across all samples is scaled to 1 for each taxon (Kelly, Shelton & Gallego, 2019). Such indexing improves our ability to track trends in abundance of individual taxa in time and space by correcting for both differences in read depth among samples and differences in amplification efficiency among sequences; mathematically, it is equivalent to the Wisconsin double-standardization for community ecology as implemented in the vegan package for R (Oksanen et al, 2013).…”
Section: Community Compositionmentioning
confidence: 99%